Aerial surveys of Canada geese and black ducks in eastern Canada - Kaczynski, Charles F.; Chamberlain, Everett B.; United States. Bureau of Sport Fisheries and Wildlife. (Washington, D.C. : U.S. Dept. of the Interior, Fish and Wildlife Service, Bureau of Sport Fisheries and Wildlife : For sale by the Supt. of Docs., U.S. G.P.O., 1968)
The visibility from aircraft of breeding black ducks is extremely low. Distribution of black ducks within the survey area is quite uniform and some apparent differences may be due to variable conditions during observations. With present resources a statistically reliable design for sampling breeding black ducks in eastern Canada is not feasible. Based on areas with consistent coverage and weighted toward annual comparability in group sizes, the black duck breeding population index appears to have been decreasing each year since 1963. Without adjustment for visibility, the index figure equals approximately one-eighth of the Atlantic Flyway winter survey figure. Canada geese show extreme variations in density in eastern Canada. The estimated number of geese in Canada east of James and Hudson Bays approximates the number of accounted for by the Atlantic Flyway winter survey and kill estimates. The extent to which the two populations are the same is unknown. This report summarizes results from aeriakl surveys of Canada geese and black ducks in eastern Canada. Information presented is based on data obtained during the summer of 1956, 1962-66 for Canada geese and during the spring of 1955, 1963-66 for black ducks. "April 1968." Includes bibliographical references (page 29). References. Summary and Discussion. Black Duck Survey - Findings. Canada Goose Survey - Findings. Methods. Introduction. Abstract. The visibility from aircraft of breeding black ducks is extremely low. Distribution of black ducks within the survey area is quite uniform and some apparent differences may be due to variable conditions during observations. With present resources a statistically reliable design for sampling breeding black ducks in eastern Canada is not feasible. Based on areas with consistent coverage and weighted toward annual comparability in group sizes, the black duck breeding population index appears to have been decreasing each year since 1963. Without adjustment for visibility, the index figure equals approximately one-eighth of the Atlantic Flyway winter survey figure. Canada geese show extreme variations in density in eastern Canada. The estimated number of geese in Canada east of James and Hudson Bays approximates the number of accounted for by the Atlantic Flyway winter survey and kill estimates. The extent to which the two populations are the same is unknown. This report summarizes results from aeriakl surveys of Canada geese and black ducks in eastern Canada. Information presented is based on data obtained during the summer of 1956, 1962-66 for Canada geese and during the spring of 1955, 1963-66 for black ducks. Mode of access: Internet.